Doses de ferro no crescimento, trocas gasosas e eficiência nutricional de mudas enxertadas de cajueiro-anão - Amorim, Francisca Frenna Verezza Rodrigues de (2019)
Cashew (Anacardium occidentale L.) plants have presented, within days of field planting, internerval chlorosis in the young leaves and, as the symptoms worsen, the leaves are completely chlorotic. These symptoms of nutritional disorder are related to cashew iron deficiency, which occur mainly due to the low availability of this micronutrient in soils and the lack of knowledge about the requirement and the response of the crop to its application. In this context, we have evaluated the effects of different iron levels of iron on the growth, photosynthetic capacity and nutritional efficiency of dwarf cashew grafted seedlings. The experiment was conducted in a greenhouse in a completely randomized design with four replications. The treatments consisted of five iron doses (0, 2.5, 5, 7.5 and 10 mg / L), using iron sulfate (20% Fe) as the source. The growth variables were evaluated: height, number of leaves, leaf area, stem diameter and dry mass (roots, shoot and total); physiological variables: photosynthesis (A), stomatal conductance (gs), transpiration (E), water use efficiency (USA), instantaneous carboxylation efficiency (EIC), photosynthetic pigments and relative chlorophyll index; and macronutrient contents: N, P, K, Ca, Mg and S; and the micronutrient Fe. The variables were subjected to analysis of variance by the F test and, when significant difference occurred, regression analysis was performed. Iron doses significantly affected the growth variables of the dwarf cashew grafted seedlings, with adjustment to the quadratic model. Fe deficiency, caused by the absence or low concentration of Fe in the nutrient solution significantly reduced nutrient accumulation, nutritional and photosynthetic efficiency of cashew seedlings. Doses ranging from 5,2 to 6,8 mg of Fe L-1 promoted higher accumulation for Fe and other evaluated nutrients and doses ranging from 4,1 to 8,2 mg L-1 of Fe promoted better photosynthetic performance. On conclusion, the 'BRS 226' dwarf cashew genotype showed good ability to absorb Fe and accumulate in roots, in contrast, demonstrated low efficiency of transporting Fe from roots to shoots, regardless of the applied dose.